The Value of Firm: The Influence of Capital Structure and Profitability in Supermarket Sub-industry Companies Listed on the Indonesia Stock Exchange for the 2018-2023 Period - Setiawan, Rudi; Hertina, Dede (Dinasti International Journal of Economics, Finance & Accounting, 2024)
One of important role for the company is the perception of the community, especially investors in shaping the company's image through the value of firm. Companies that are able to manage resources efficiently will be more successful in increasing their value of firm. Therefore, the purpose of this study is to analyze the effect of Debt to Equity Ratio, Return on Assets, Return on Equity, and Net Profit Margin partially on Price to Book Value in supermarket sub-industry companies listed on the Indonesia Stock Exchange for the 2018-2023 period. The method used is quantitative descriptive method with the data used is secondary data which is annual financial reports. The data analysis technique uses panel data regression techniques through Eviews 12. The results of this study indicate that Debt to Equity Ratio and Return on Equity have no effect on Price to Book Value, Return on Assets has a positive and significant effect on Price to Book Value, and Net Profit Margin has a negative and significant effect towards Price to Book Value.